New loss of smell and taste: Uncommon symptoms in COVID-19 patients on Nord Franche-Comte cluster, France. (November 2020) - Klopfenstein, Timothée; Zahra, Hajer; Kadiane-Oussou, N'dri Juliette; Lepiller, Quentin; Royer, Pierre-Yves; Toko, Lynda; Gendrin, Vincent; Zayet, Souheil
Highlights: New loss of taste or smell was not included as common symptoms of COVID-19 until March 2020 when the pandemic started in Western countries. It is interesting to know the prevalence of such symptoms and how they were related to disease severity and prognosis. In our study including 70 patients, anosmia and dysgeusia were present in half of COVID-19 patients. The mean duration of anosmia was 7 days and the outcome seems favorable in less than 28 days. Abstract: Background: New loss of smell or taste was not included as common symptoms of COVID-19 until March 2020 when the pandemic started in Western countries. We want to describe the prevalence and features of anosmia and dysgeusia in COVID-19 patients. Methods: We retrospectively investigated the clinical features of confirmed cases of COVID-19 in Nord Franche-Comté Hospital, Trevenans, France, between March, 1st and March, 14th 2020. We used SARS-CoV-2 real time RT-PCR in respiratory samples to confirm the cases. Results: Of 70 patient enrolled, the mean age was 57.0 years and 29 patients (41%) were men. Median Charlson comorbidity index was 1.70(±2.5). Twenty-seven (39%) patients had pneumonia. Fatigue (93% [65]), cough (80% [55]) and fever (77% [54]) were the three main symptoms. Neurologic symptoms were present in more than half of the patients: anosmia (53% [37]) and dysgeusia (48% [34]). The mean duration of anosmia was 7.4 (±5, [1–21]) days, 51% (36/70) recovered before 28 days of evolution. Only one patient with anosmia had not recovered at the end of the follow-up. Patients with anosmia had less often a pneumonia (10/37 vs 17/33, p = 0.036), were less often hospitalized (13/37 vs 20/33, p = 0.033) and needed less often oxygen therapy (6/37 vs 17/33, p = 0.002) than patients without anosmia. There were no statistically differences for viral load between patients with anosmia and patients without anosmia (5.5 [2.0–8.6] vs 5.3 [2.1–8.5] log copies/ml respectively, p = 0.670). The fatality of COVID-19 in our study was 6% with four deaths. Conclusions: Anosmia and dysgeusia are present in half of COVID-19 patients. The mean duration of anosmia was 7 days and the outcome seems favorable in less than 28 days.